Excited delirium syndrome : cause of death and prevention - Di Maio, Theresa; Di Maio, Vincent J. M., 1941- (Boca Raton : CRC/Taylor & Francis, 2006)
A suspect, prisoner, or psychiatric patient becomes violent. The officer or hospital staff struggle to control the person, sometimes with a choke hold or hog tying. Shortly afterward, the patient dies. This illustrates excited delirium syndrome, a condition in which normal physiological changes produced by violent activity culminate in sudden cardiac death. This book discusses the effects of both legal medication and drugs of abuse on the cardiovascular system. The authors also discuss the effects of underlying disease and prevention of the syndrome, the role of the mental health professional, and the'high-risk' individual
Preface - Acknowledgments -- 1. Introduction to death due to excited delirium syndrome -- 2. History of excited delirium syndrome -- 3. Traditional explanations for death due to excited delirium syndrome -- 4. Physiological reactions to stress -- 5. Effects of drugs on the heart, brain, and sympathetic nervous system -- 6. Synthesis of physiological reactions to stress, natural disease, drugs of abuse, and medications in cases of excited delirium -- 7. Medcio-legal investigations of death due to excited delirium syndrome -- 8. Cases of excited delirium syndrome -- 9. Prevention of excited delirium syndrome : the police and first responders -- 10. Sudden death of the psychiatric patient in mental health facilities -- Index
Includes bibliographical references and index
Keywords: Delirium -- diagnosis; Psychoses, Substance-Induced -- diagnosis; Death, Sudden, Cardiac -- etiology